Prediction of Customer Buying Intention due to Chatbot System: Application of TAM Model - Dr. Bharti Motwani (International Journal of Advanced Science and Technology, 2020)
The purpose of this research paper is to determine the true picture of chatbot system with respect to buying behaviour of customer. Four factors related to TAM model of chatbot system namely Perceived Usefulness, Security, Attitude and Ease of Use are considered as independent variables, while intention related to buying of product is considered as dependent variable. All the factors were found to be contributing to the buying intention. Non probability judgmental sampling method was used for the collection of primary data from 924 respondents. Various machine learning algorithms including gradient boosting, random forest, logistic regression, naïve bayes and decision tree and were used to develop, train and test the model. Highest accuracy was found to be from the random forest and gradient boosting algorithm.